Soluble Intercellular Adhesion Molecule- (sICAM-) 1, Thrombospondin-1, and Vinculin for the Identification of Septic Shock Patients Suffering from an Invasive Fungal Infection. (7th January 2020) - Decker, Sebastian O.; Incamps, Anne; Sigl, Annette; Uhle, Florian; Bruckner, Thomas; Heininger, Alexandra; Zimmermann, Stefan; Hirtz, Christophe; Weigand, Markus A.; Brenner, Thorsten
Abstract : Background . Nowadays, invasive fungal infections (IFI) are of increasing importance and associated with an increased mortality. However, reliable diagnostic tools for the identification of patients suffering from an IFI are rare and associated with relevant weaknesses. Methods . Within this secondary analysis of an observational clinical study, an innovative biomarker panel (consisting of 62 biomarkers in total) was screened for the identification of septic shock patients suffering from an IFI. Fungal growth in blood cultures, intraoperative swabs, and Aspergillus spp. in deep respiratory tract specimens with accompanying pulmonary infiltrates were classified as infection, whereas Candida spp. in the respiratory tract or in fluids from drainages were classified as colonization. Plasma samples of 50 septic shock patients at six predefined timepoints within a period of 28 days following the onset of septic shock were available. Results . In total, 11 out of the 50 patients (22%) were shown to suffer from an IFI, whereas 22 patients (44%) presented with a fungal colonization. Within the presented biomarker panel, plasma levels of soluble intercellular adhesion molecule- (sICAM-) 1, thrombospondin-1, and vinculin were shown to be the most promising. sICAM-1 was shown to be increased in patients with an IFI, whereas thrombospondin-1 and vinculin revealed decreased plasma levels as compared to colonized patients as well as patients without any fungal findings at any time. Conclusion . Plasmatic measurements of sICAM-1, thrombospondin-1, and vinculin may help to facilitate the diagnosis of an IFI in human septic shock and to identify patients with an increased risk for an IFI. This trial is registered with DRKS00005463 .